2017
DOI: 10.1186/s13045-017-0520-1
|View full text |Cite|
|
Sign up to set email alerts
|

Interim analysis of survival in a prospective, multi-center registry cohort of cutaneous melanoma tested with a prognostic 31-gene expression profile test

Abstract: BackgroundA 31-gene expression profile (GEP) test that provides risk classification of cutaneous melanoma (CM) patients has been validated in several retrospective studies. The objective of the reported study was a prospective evaluation of the GEP performance in patients enrolled in two clinical registries.MethodsThree-hundred twenty two CM patients enrolled in the EXPAND (NCT02355587) and INTEGRATE (NCT02355574) registries met the criteria of age ≥ 16 years, successful GEP result and ≥1 follow-up visit for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 30 publications
4
70
0
Order By: Relevance
“…The test assesses the expression of three control genes, four genes with proven prognostic utility for UMs [31] and 24 genes previously reported to be differentially expressed in metastatic compared to primary tumours [32][33][34][35][36][37][38]. The performance of this test has been evaluated in several retrospective [30,39,40] as well as prospective validation studies [41,42] and has been shown to enhance current prognostic accuracy in particular through identifying clinically and pathologically sentinel lymph node (SLN)-negative patients with high-risk of metastases. However, although there is great promise in reproducibility and clinical validity, the clinical utility for the 31-GEP test on clinical decision-making is still incompletely defined, and will require evidence from further large-scale prospective multi-institutional registry studies before it can be considered for inclusion in any national or professional association guideline recommendations.…”
Section: Gene Expression Profiles and Their Prognostic Implicationmentioning
confidence: 99%
“…The test assesses the expression of three control genes, four genes with proven prognostic utility for UMs [31] and 24 genes previously reported to be differentially expressed in metastatic compared to primary tumours [32][33][34][35][36][37][38]. The performance of this test has been evaluated in several retrospective [30,39,40] as well as prospective validation studies [41,42] and has been shown to enhance current prognostic accuracy in particular through identifying clinically and pathologically sentinel lymph node (SLN)-negative patients with high-risk of metastases. However, although there is great promise in reproducibility and clinical validity, the clinical utility for the 31-GEP test on clinical decision-making is still incompletely defined, and will require evidence from further large-scale prospective multi-institutional registry studies before it can be considered for inclusion in any national or professional association guideline recommendations.…”
Section: Gene Expression Profiles and Their Prognostic Implicationmentioning
confidence: 99%
“…This test has been validated in several historical cohorts showing that its prognostic ability is independent from the clinical and pathological features of the tumour. [15][16][17][18][19][20][21][22][23][24] However, this test has never before been evaluated in a prospective multicentre cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in MSS between patients with class 1 and class 2 tumors, having stage I to IIA disease, was significant (HR, 6.13; 95% CI, 1.07‐35.24; P = 0.04). The class 2 association with high‐risk disease has been further validated in both a single‐center prospective study that reported a 5‐year RFS rate of 68.7% for class 2 patients, and a multicenter prospective analysis that reported class 2 RFS rates of 77% in a cohort 1.5 years median follow up …”
Section: Biomarkersmentioning
confidence: 92%
“…Genes included in the 31‐GEP were distilled from a comparative review of multimarker studies performed between 2000 and 2011, from which over 150 genes associated with recurrence were identified . The test includes three control genes and 28 prognostic genes that have been validated in three multicenter retrospective cohorts, two prospective studies, and an analytic analysis that reported robust reproducibility of the test (98% technical success rate in 8244 clinically tested specimens) . Unlike the tests described above, the 31‐GEP uses radial basis machine (RBM) pattern recognition modeling to compare the GEP of a test sample to a training set containing 164 melanoma tumors with known outcomes.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation